Kepuasan Pengguna Aplikasi Pasti Oke Melalui Kualitas Pelayanan E-Government di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Garut - Hadita, Akmala; Agustina, Novi; Bella, Sintia (Institut Teknologi Garut, 2025)
This study aims to analyze the effect of e-government service quality on user satisfaction of the Pasti Oke Application at the Garut Regency Population and Civil Registration Office. This application is designed to improve the efficiency of population administration services digitally. However, in its implementation, there are still various obstacles such as difficult accessibility, system disruptions, lack of clarity of information, and low response from the application manager. The research method used is a quantitative approach with simple linear regression analysis using SPSS 23. Data were collected through questionnaires distributed to 100 respondents who used the application. The results show that the quality of e-government services has a significant influence on the level of user satisfaction with a contribution of 71.6%. These results provide important implications for the development of more effective and responsive public digital services.